ANALISIS PERILAKU DALAM MELAKSANAKAN PROGRAM 3R (REDUCE, REUSE, RECYLE) TERHADAP BERBAGAI JENIS SAMPAH BOTOL PLASTIK PADA MAHASISWA UNIVERSITAS JEMBER - Muhammad Nidhomul haq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
This study aims to carefully analyze the social behavior in properly implementing the 3R program (reducing, reusing, recycling) various types of plastic bottle waste. This social problem is indicated to Jember University students who frequently employ various types of plastic bottles in their ordinary life. This published article was carefully compiled using literature study research methods and quantitative surveys. Data collection is typically done by typically taking specific references in peer-reviewed journals, published articles and local news. The survey was conducted by distributing questionnaires to students using a google form via the WhatsApp application. Typically based on the extant literature, it is proven that by implementing the 3R program (reducing, reusing, recycling), students are able to reduce environmental pollution at the University of Jember due to the use of various types of plastic bottle waste. With extensive research on the analysis of student behavior towards various types of plastic bottle waste, we can find out the level of awareness of Jember University students about the importance of preserving the environment and how they are trying to reduce the impact of global warming on the campus environment.